THE EFFECT OF MINDSET AND MOTIVATION ON GRIT BECAME ACCOUNTANT OF ACCOUNTING STUDENTS UNIVERSITY IN JAKARTA - Pebrian, Rizky; Susanti, Santi; Sumiati, Ati (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2020)
This study aims to find out whether there is an influence between Mindset and Motivation with Grit of Students University in Jakarta. The Study was conducted for three months staring from November 2019 until January 2020. The research method used survey method. The Population in this research is 320 accounting students of University in Jakarta. The Sampling technique used random sampling so that the sample was 167 students. Data of variable (Y) Grit, (X1) Mindset, and (X2) Motivation were obtained from the questionnaire. The requirements analysis test done is to find regression equation that produces Ẏ = 5,177 + 0,477X1 + 0,677X2. The results of analysis show: (i) there is significant positive influence between mindset with grit, (ii) there is significant positive influence between motivation and grit, (iii) there is significant positive influence between mindset and motivation with grit. Basic on the results of the analysis it can be concluded that mindset and motivation stimultaneously affect grit.